Interprofessional simulation of birth in a non-maternity setting for pre-professional students. (November 2017) - McLelland, Gayle; Perera, Chantal; Morphet, Julia; McKenna, Lisa; Hall, Helen; Williams, Brett; Cant, Robyn; Stow, Jill
Abstract: Background: Simulation-based learning is an approach recommended for teaching undergraduate health professionals. There is a scarcity of research around interprofessional simulation training for pre-professional students in obstetric emergencies that occur prior to arrival at the maternity ward. Objectives: The primary aims of the study were to examine whether an interprofessional team-based simulated birth scenario would improve undergraduate paramedic, nursing, and midwifery students' self-efficacy scores and clinical knowledge when managing birth in an unplanned location. The secondary aim was to assess students' satisfaction with the newly developed interprofessional simulation. Design: Quasi-experimental descriptive study with repeated measures. Setting: Simulated hospital emergency department. Participants: Final year undergraduate paramedic, nursing, and midwifery students. Methods: Interprofessional teams of five students managed a simulated unplanned vaginal birth, followed by debriefing. Students completed a satisfaction with simulation survey. Serial surveys of clinical knowledge and self-efficacy were conducted at three time points. Results: Twenty-four students participated in one of five simulation scenarios. Overall, students' self-efficacy and confidence in ability to achieve a successful birth outcome was significantly improved at one month ( p  < 0.001) with a magnitude of increase (effect) of 40% ( r  = 0.71) and remained so after a further three months. Clinical knowledge was significantly increased in only one of three student groups: nursing ( p  = 0.04; r  = 0.311). Students' satisfaction with the simulation experience was high ( M  = 4.65 / 5). Conclusions: Results from this study indicate that an interprofessional simulation of a birth in an unplanned setting can improve undergraduate paramedic, nursing and midwifery students' confidence working in an interprofessional team. There was a significant improvement in clinical knowledge of the nursing students (who had least content about managing birth in their program). All students were highly satisfied with the interprofessional simulation experience simulation. Highlights: Evaluation of birthing skills of paramedic, nursing and midwifery students in a non-maternity simulated context. Although interprofessional simulation learning rated highly by students, more research required for more representative data. The interprofessional birthing simulation scenario is recommended for undergraduate health curricula.